SOSIALISASI (EDU FAIR) PERAN PERGURUAN TINGGI DALAM MENINGKATKAN PROFESIONALISME SDM PERUSAHAAN - Heri Sasono; Iman Santoso (BADAN PENERBIT STIEPARI PRESS, 2022)
Socialization of the role of Higher Education (Edu Fair), especially STIE Dharma Bumiputera, Jakarta to employees of the Bumiputera Group (AJB Bumiputera 192, PT. Bumida, PT. Bumi Wiyata), approximately 30 participants (Employees), so that they are interested and interested in continuing to Level higher education (Master in Management/MM). After participating in the Edu Fair, employees are expected to continue on to a higher level of education, without leaving their job (still working). The benefit for the company is that the company has employees who are professional, creative, critical, have broad insight and experience, have good knowledge. The Company can accelerate the achievement of the Vision, Mission of the company that has been set by the Founder and Top Management, so that the welfare of the Employees increases, in the end Loyal Employees and the Company remain Survive and can win in business competition.